Controllable Preparation of Holey Graphene and Electrocatalytic Performance for Oxygen Reduction Reaction. (20th February 2017) - Lv, Ruijing; Wang, Hongjuan; Yu, Hao; Peng, Feng
Graphical Abstract: Highlights: The size and the density of holes on graphene are controlled by a simple method. The formation mechanism of holey graphene is proposed. Holey graphene shows good activity and stability for oxygen reduction reaction (ORR). The defects, conductivity and ORR performance are quantitatively correlated. Abstract: Defects or pinholes in graphene are important for tuning its properties to be applicable in various fields, such as supercapacitor and oxygen reduction reaction (ORR). Here, we report a simple carbothermal method to controllably form defects or pinholes in graphene by reacting graphene with CoOx in argon atmosphere. The morphology of defects or pores and the reaction mechanism were investigated and discussed detailedly. The defects, the conductivity and the ORR performance in alkaline electrolyte of the holey graphene were quantitatively analyzed and correlated. The results show that the optimized annealing temperature is 700 °C based on the ORR activity. The content of defects or edge carbon atoms of holey graphene, that is the defect density ( n D ), determining factor for the ORR activity, can be controlled by controlling the pore size and the density in the basal plane of graphene that was realized by adjusting the cobalt content in the precursor. 10Co/G-700-HCl, possessing the highest edge or defective carbon content, reveals the optimal ORR performance with mixed 4e − and 2e − ORR process, excellent stability and good methanol tolerance.